Salem falls : a novel - Picoult, Jodi. (New York : Atria Books, 2007)
Robbed of his teaching career and reputation by a student's false accusations, Jack St. Bride is struggling to rebuild his life, but fresh accusations of rape by teenage girls from his former school threaten to destroy him again
Keywords: Diners (Restaurants) -- Fiction; Electronic books